2017
DOI: 10.4186/ej.2017.21.3.63
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Biochar Prepared from Acacia Wood and Coconut Shell for Soil Amendment

Abstract: Abstract. The biochar produced from the agricultural wastes was aimed to amend the extreme degraded soil. The properties of biochar prepared from Acacia wood and coconut shell were investigated by different pyrolysis conditions in order to identify the suitable initial biomass of biochar applied for sandy soil amendment. The slow pyrolysis was applied for preparing biochar under different conditions. The temperature was varied from 300, 400 and 500 o C meanwhile the pyrolysis times were varied to 1, 2 and 3 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…Meanwhile, the percentage of hydrogen in BPS biochars are very low due to the loss of hydrogen component during the pyrolysis process of BPS feedstock. The feedstock loses surface functional –OH groups due to dehydration at lower pyrolysis temperatures and loses H atoms due to the structural core degradation [ 83 ]. The result also revealed that BPS biochar contained 28.48% and 19.96% of nitrogen for biochar derived from fast and slow pyrolysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the percentage of hydrogen in BPS biochars are very low due to the loss of hydrogen component during the pyrolysis process of BPS feedstock. The feedstock loses surface functional –OH groups due to dehydration at lower pyrolysis temperatures and loses H atoms due to the structural core degradation [ 83 ]. The result also revealed that BPS biochar contained 28.48% and 19.96% of nitrogen for biochar derived from fast and slow pyrolysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was also examined that the concentration of total phenolics was increased than that of proteins which indicated more regulation of total Cr and Pb stress because phenolics are involved in ROS scavenging ( Figure 4 ). The improvement in biochemical compounds of plants might be due to the increase in the water-holding capacity of soil with the applications of chitosan and rice husk biochar (Pandey and De, 2017 ; Pituya et al, 2017 ; Suliman et al, 2017 ). Therefore, the production of starch, amino acids, proteins, phenolics, carotenoids, and chlorophyll content is enhanced by the improvement of the plant's metabolic activities due to the improved flow of water through the xylem toward the leaves (Younis et al, 2015 ; Hafeez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…4). The biochar used in this study (B and BS) has a high water-holding capacity (400% and 250%) compared to other biochar compounds, for example, the water-holding capacity of coconut shell biochar is 60% (Pituya et al, 2017;Paul and Harikumar, 2022). This WHC of sun ower biochar is due to the superabsorbent materials of the sun ower stalk, (pith brous and hemicellulose).…”
Section: Soil Water Contentmentioning
confidence: 99%